Associations between serum levels of Polybrominated Diphenyl Ether (PBDE) flame retardants and environmental and behavioral factors in pregnant women - Buttke, Danielle E. (J Expo Sci Environ Epidemiol, 2012)
BACKGROUND: Polybrominated diphenyl ethers (PBDE) are flame retardants that were previously used in upholstery, fabrics, and household appliances. PBDEs have been linked to adverse health outcomes, including neurotoxicity, thyroid hormone dysregulation, endocrine disruption, and poor semen quality. Because PBDEs pass into placental circulation, maternal exposures can approximate fetal exposures. OBJECTIVES: Our objectives were to determine if diet and specific human behaviors were significantly associated with PBDE exposures in a cohort of pregnant women. METHODS: Women between the 34(th) and 38(th) week of pregnancy were given a questionnaire about behavioral, environmental, and dietary factors and asked to provide blood samples. Serum PBDE levels were measured using GS-MS and lipid adjusted. An adjusted ordinary least squares regression model was run to identify potential associations between behaviors and serum PBDE levels. RESULTS: Serum concentrations of BDEs 47, 99, 100, and 153 were found above the limit of detection in at least 50% of study participants and used in our models. Associations with serum PBDEs were observed with self-reported hand-to-mouth behaviors, including biting nails and licking fingers. Serum BDE levels of 47, 99, 153, and total PBDEs were also significantly higher in those individuals owning a large screen TV compared to those who did not. Serum PBDE levels were comparable to levels reported in the general population. CONCLUSIONS: Hand-to-mouth behaviors may influence serum PBDE concentrations in adults. Household electronics such as large-screen TV’s appear to serve as a significant source of PBDEs in pregnant women. Together, hand-to-mouth behaviors and TV ownership may serve as a route of exposure to PBDEs in adults.